Semantics Analysis - Nur Lailatul Aqromi (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2019)
Meaning concepts is always being an interesting topic in linguistics especially about antonymy. Antonymy is not only found in absolute term but also in other ones. This research then tried to discuss antonymy in Bahasa Indonesia particularly in military terms, time and taste terms. The method used was Relation by Contrast-Lexical Contrast (RC-LC). Furthermore, as the result it was found that antonymy had some variants such as: non binary antonymy, contrastive antonymy, and gradation antonymy.